#### Answer

Consider the equation
$$\sqrt{x+2}=3-\sqrt{x-1}$$
Squaring the left side and simplifying results in $x+2$
Squaring the right side and simplifying results in $x-6\sqrt{x-1}+8$

#### Work Step by Step

The equation given is
$$\sqrt{x+2}=3-\sqrt{x-1}$$
Squaring the left side results in the elimination of the square root, so the first answer is:
$(\sqrt{x+2})^{2}=x+2$
The right side is a binomial, squaring it and simplifying produces the following expression:
$(3-\sqrt{x-1})^{2}=9-(2)(3)(\sqrt{x-1})+(\sqrt{x-1})^{2}=...$
$...=9-6\sqrt{x-1}+x-1=...$
$...=x-6\sqrt{x-1}+8$